Busytown race day - Scarry, Richard (New York : Aladdin Paperbacks, 1995)
It's the annual Busytown Race Day, and the Huckle and Lowly are ready to go. Then disaster strikes!
Keywords: Racing-Fiction; Cars-Fiction; Animals-Fiction